Characteristics and Toxicity of an Everyday Polyamide : A study of potential health risks of micro- & nanoplastics released from nylon - Boo,Kevin (2025)
Plastic has been a revolutionary material in human history. Plastic materials have several desirable properties, such as durability, low production costs, and versatility. This helps explain the increase in their use and production over the past 100 years. Plastics are synthetic polymers, with long repeating chains of monomers; this creates structures that are chemically stable and durable. The overconsumption of plastics has, however, made these desirable properties a burden. Plastics are hard to break down and recycle and do so very slowly in natural pathways. This means that the issue of plastic pollution grows, leading to environmental damage. Recent studies have also shown that there are micro- and nanoplastics that are released from plastic pollution, which end up in the brain and other organs, because these plastic particles can cross natural barriers due to their small size and unique properties. In this study we focus on oven bags, a nylon-based cooking utensil. The oven bag is exposed to mechanical weathering and heat while being in direct contact with food. This could lead to the release of micro- and nanoplastics from the oven bag, which would get directly released into the food and liquids inside the oven bag. The study looks at physical and chemical characteristics of the released particles in relation to potential toxicity that could occur. This is done with D. magna toxicity tests, NTA analysis, TEM-imaging and FTIR-spectroscopy. The results show that toxicity occurs when the oven bag is baked. Other processing methods generally extended the life of D. magna. There is significant proof that PA micro- and nanoparticles can cause toxicity which is heat dependent. Furthermore, oven bags that are cooked at higher temperatures cause more toxicity. Particles that were already released could not become toxic retroactively due to high temperatures.
Keywords: Nanoplastics; Microplastics; toxicity; daphnia magna; algae; nylon; polyamide; plastics; toxicity tests; oven bag; biophysical chemistry